A genealogy of an ethnocratic present: rethinking ethnicity after Sri Lanka’s civil war - Schubert, Stefan Andi (Kansas State University, 2016)
The presence and persistence of ethnicity in Sri Lanka has led scholars such as Jayadeva Uyangoda to describe Sri Lanka as an “ethnocracy” and is identified as one of the major challenges for attempts to reconcile communities after a 26-year-long civil war that ended in 2009. The emphasis on ethnicity, however, often makes it difficult for scholars to examine the discontinuities that have shaped the emergence of ethnicity as the most significant social category in the country. This thesis addresses this lacuna by providing a careful re-reading of the conditions under which ethnicity became the focus of both politics and epistemology at the turn of the 20th century in colonial Ceylon. Michel Foucault’s conceptualization of governmentality enables this examination by demonstrating how ethnicity became the terrain on which political rationalities and governmental technologies were deployed in order to shift how populations were constructed as the focus of colonial governance between 1901 and 1911. Colonial political rationalities are explored through an examination of the debate that emerged in the Census reports of P. Arunachalam (1902) and E.B. Denham (1912) over whether Ceylon is constituted by many nationalities or by one nationality—the Sinhalese—and many races. The emergence of this debate also coincided with the Crewe-McCallum Reforms of 1912 which aimed to reform the colonial state in response to the demands of the local population. Like the debate between Arunachalam and Denham, what is at stake in the reforms of 1912 is the question of whether the Island is constituted by many racial populations or a single population. The terms of these debates over ethnicity that took place over a century ago, continue to shape the tenor of Sri Lanka’s post-war political landscape and therefore provides a pathway for understanding how Sri Lanka’s post-war challenges are imbricated in the dilemmas of inhabiting its colonial present(s).
Keywords: Sri Lanka; Michel Foucault; Ethnicity; Post-war; Colonialism; Governmentality